Arellano Ibarra,Ketty Vanessa(2023)Evaluación in vitro de la infección de Phytophthora palmivora en tres materiales de cacao (Theobroma cacao L.) del litoral ecuatoriano.Quevedo.UTEQ.103p. - Arellano Ibarra , Ketty Vanessa (2023)
Cocoa is one of the main crops in Ecuador, however, it is attacked by a disease known as black pod caused by the generation of a complex of fungi of the genus Phytophthora. The present investigation focuses on evaluating the infection of Phytophthora palmivora under controlled conditions in pods and seedlings of three cocoa materials from the Ecuadorian coast. To measure the external infection of P. palmivora, healthy ears of CCN-51, Nacional and Trinitario were used at an intermediate physiological maturity. Seeds of the materials were also used. The results of the experiments carried out on ears revealed the susceptibility of CCN-51 after 6 days of inoculation with P. palmivora, reaching the highest averages, while the other materials (National and Trinitario) presented lower averages, these being the less susceptible. The reactions of the biochemical tests carried out on the seedlings after 65 days post inoculation showed a generation of these enzymes when the pathogen was present in the 2 inoculation methods. The inoculations of P. palmivora at the edaphic and foliar level in Nacional and Trinitario cacao seedlings do not show critical symptoms, however, it was possible to demonstrate a high infection rate in CCN-51, being an unsuitable material for its use in vegetative propagation.